50.3k views
0 votes
What is (f+g)(x)?{f(x)=2x^3-4xg(x)=x^3+2x^2-10Write you answer in standard form.

User Gitty
by
5.0k points

1 Answer

4 votes
Answer:
(f+g)(x)=3x^3+2x^2-4x-10Step-by-step explanation:

The given functions are:


\begin{gathered} f(x)=2x^3-4x \\ g(x)=x^3+2x^2-10 \end{gathered}
(f+g)(x)=f(x)+g(x)
(f+g)(x)=(x^3+2x^2-10)+(2x^3-4x)

Simplify the resulting function


\begin{gathered} (f+g)(x)=x^3+2x^3+2x^2-4x-10 \\ (f+g)(x)=3x^3+2x^2-4x-10 \end{gathered}

The final function in standard form is:


(f+g)(x)=3x^3+2x^2-4x-10

User Rob Fonseca
by
4.8k points